Energy efficiency evaluation of a centralised wastewater treatment plant in an industrial zone of former Binh Duong province, Vietnam - Vinh Thi Nguyen; Le Hung Anh; Trung Minh Dao; Thang Anh Nguyen; Tan Thanh Le (Vietnam Journal of Science, Technology and Engineering)
Efficient energy utilisation in wastewater treatment plants is a significant challenge for management, particularly in developing countries. This study presents an integrated approach combining energy auditing, real-time monitoring, and energy assessment to optimise industrial wastewater treatment plant operations in Vietnam, with a treatment capacity of under 4,000 m³/day. The research methodology employs an energy audit approach combined with daily measurements, analysing the plant’s operational data for 2023. Results indicate that the aerobic tank consumes the most energy (56.1% of total plant consumption). Wastewater pumps, blowers, mixers, and sludge pumps consume a substantial amount of electricity (77.6% of total electricity consumption). The average specific energy consumption is 0.93 kWh/m³ of treated wastewater, 10.58 kWh/kg CODremoved, and 59.12 kWh/kg TNremoved, which are 15-20% higher than international benchmarks for similar-scale facilities. Based on the analysis, we propose optimisation strategies: (1) improving operating conditions and flexibility; (2) optimising the blower system for aerobic tanks; (3) upgrading to energy-efficient pumps; (4) enhancing lighting, automatic monitoring, and office systems; (5) integrating renewable energy sources. These interventions could reduce energy consumption by 25-30% while maintaining treatment The research findings will enhance the plant's energy efficiency, reduce operational costs, and support Vietnam's goal of achieving net-zero emissions by 2050. efficiency.